Antimicrobial Prescribing Practices in Small Animal Emergency and Critical Care - Robbins, Sarah N.; Goggs, Robert; Lhermie, Guillaume; Lalonde-Paul, Denise F.; Menard, Julie (Frontiers in Veterinary Science, 2020)
Background: Antimicrobial use contributes to emergence of antimicrobial resistance. It was hypothesized that antimicrobial prescribing behavior varies between the emergency (ER) and critical care (CC) services in a veterinary teaching hospital. This study aimed to: i) describe antimicrobial prescribing patterns in the ER and CC services; ii) assess adherence to stewardship principles; iii) evaluate the prevalence of multidrug resistant (MDR) bacterial isolates. Methods: Institution electronic medical records were queried for all antimicrobial prescriptions from the ER and CC services between 1/1/2017-12/31/2017. Prescriptions were manually reviewed, and the following data recorded: drug, dosage, duration, diagnosis, outcome, hospitalization duration, culture submission and susceptibility results. Results: There were 5091 ER visits, of which 3125 were not transferred to another service. Of these emergency visits, 516 (16.5%) resulted in 613 antimicrobial drug prescriptions. The most commonly prescribed drugs were amoxicillin/clavulanate (n=243, 39.5%), metronidazole (n=146, 23.7%) and ampicillin/sulbactam (n=55, 8.9%). The most common reasons for antimicrobial prescriptions were gastrointestinal disease, skin disease (both n=111, 21.4%) and respiratory disease (n=77, 14.8%). For ER patients 17 cultures were submitted (3.2%) and 1 MDR organism was isolated. The CC service managed 311 patients for 822 patient days. Of these, 133 case visits (42.7%) resulted in 338 prescriptions. The most commonly prescribed drugs were ampicillin/sulbactam (n=103, 30.4%), enrofloxacin (n=75, 22.1%) and metronidazole (n=59, 17.4%). The most common reasons for antimicrobial prescriptions were gastrointestinal disease (n=25, 18.8%), respiratory disease (n=21, 15.7%) and sepsis (n=17, 12.7%). On the CC service, 49 patients had ≥1 culture submitted (36.8%) and 12 MDR organisms were isolated. Of patients prescribed antimicrobials, 15/38 (39.5%) with urinary tract disease, 2/28 (7.1%) with pneumonia, 1/11 (9.1%) with canine infectious respiratory disease complex and 2/8 (25%) with feline upper respiratory infection were compliant with published guidelines. Conclusions: Antimicrobial prescription was common in both ER and CC services and followed similar patterns. MDR organisms were frequently encountered. Adherence to published guidelines for urinary and respiratory infections was poor.